CB2-deficiency is associated with a stronger hypertrophy and remodeling of the right ventricle in a murine model of left pulmonary artery occlusion - Duerr, Georg Daniel; Feisst, Andreas; Halbach, Katharina; Verfuerth, Luise; Gestrich, Christopher; Wenzel, Daniela; Zimmer, Andreas; Breuer, Johannes; Dewald, Oliver (Life Sciences, 2018)
Aims: Pulmonary hypertension (PH) leads to right ventricular (RV) adaptation and remodeling and has deleterious long-term effects on RV function. The endocannabinoid receptor CB2 has been associated with protective effects in adaptation and remodeling of the left ventricle after ischemia. Therefore, we investigated the role of CB2 receptor in RV adaptation after occlusion of the left pulmonary artery (LPA) in a murine model. Main methods: C57/Bl6 (WT)- and CB2 receptor-deficient (Cnr2−/−)-mice underwent paramedian sternotomy and LPA was occluded using a metal clip. Right heart hemodynamic study (Millar®) preceded organ harvesting for immunohistochemistry and mRNA analysis 7 and 21 days (d) post-occlusion. Key findings: LPA occlusion led to higher RV systolic pressure in Cnr2−/−-hearts, while hemodynamics were comparable with WT-hearts after 21d. Cnr2−/−-hearts showed higher macrophage infiltration and lower interleukin-10 expression after 7 d, but otherwise a comparable inflammatory mediator expression profile. Cardiomyocyte-hypertrophy was stronger in Cnr2−/−-mice, presenting with higher tenascin-C expression than WT-hearts. Planimetry revealed higher collagen area in Cnr2−/−-hearts and small areas of cardiomyocyte-loss. Surrounding cardiomyocytes were cleaved caspase-3- and TUNEL positive in Cnr2−/−-hearts. This was associated by maladaptation of myosin heavy-chain isoforms and lower reactive oxygen scavenger enzymes induction in Cnr2−/−-hearts. We found comparable morphological changes in both lungs between the two genotypes. Significance: LPA occlusion led to increased systolic pressure and adaptation of RV in CB2-deficient mice. CB2 receptor seems to modulate RV adaptation through expression of contractile elements, reactive oxygen scavenger enzymes, and inflammatory response in order to prevent cardiomyocyte apoptosis.
CRIS-Team Scopus Importer:2022-05-03
Keywords: Cardiac remodeling; Endocannabinoids; Pulmonary hypertension